“SIR” APPROACH (SENSITIVE, IMAGINATIVE AND RATIONAL) TO APPRECIATING AN ARTWORK (Palíndromo, 2024)
Appreciating an artwork is a complex activity that requires the development of skills: skills to exploit one's imagination; skills to exploit one’s sensitivity; skills to examine a work of art. It also requires skills to synthesize what has been felt, imagined and examined. The article presents the “SIR” approach, a proposal for appreciating works of art according to three stages, in this order: 1) feeling and imagining; 2) examine the content elements and sociocultural elements of the artwork; 3) summarize the first two steps to establish a critical and aesthetic judgment. It is an appreciation process that can be carried out by art teachers and other educators and aims to develop sensitive, imaginative, analytical and synthetic skills.
Keywords: Art/education; Aesthetic appreciation; Visual Literacy; Sensibilit